Stratification of Risk of Tuberculosis in People's Councils of Cienfuegos Municipality - Hilda María Delgado Acosta; Lídice González Moreno; María Lina Valdés Gómez; Sara Hernández Malpica; Tamara Montenegro Calderón; Delfín Gerónimo Rodríguez Buergo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Background: the process of epidemiologic stratification is used as a base to categorize methodologically and in integral manner groups of population according to risk factors. Objective: accomplishing the stratification of risk of pulmonary tuberculosis in People's Councils of Cienfuegos municipality. Methods: a descriptive study in 18 People's Councils, from 2007 to 2011 was conducted. The information got from the departments of statistics of the areas of health and Municipal Hygiene and Epidemiology units. To stratify the risks the criteria of the provincial commission of tuberculosis, the incidence of the disease in the last five years in the province and the measure of the prevalence of risk factors according to dispensarization of the year 2011 were taken into account. By means of program MapInfo 7, 5, the People's Councils were classified as high, medium and low risk according to the moral values of the median of the incidence of cases and the average of contacts of patients white pulmonary tuberculosis, virus's prevalence of acquired been immunodeficiency, former imprisoned population, alcoholics, social cases, bigger population of 60 years and prevalence of diabetes mellitus. Results: three People's Councils were identified as high risk, 13 of medium risk and two of them as low risk. The People's Councils classified as high risk were: Historic Center, Punta Gorda and San Lázaro that represented the 16.7 %. Conclusion: a space dispersion of risk of pulmonary tuberculosis at Cienfuegos Municipality was observed that represents an increment of the probability of the disease.